Urgensi Islamisasi Sains Dalam Menghadapi Mordenisasi; Pendekatan Teologis - Yunita Hariyani (Al Hikmah: Jurnal Studi Keislaman, 2019)
Abstract, this research aims to neutralize the influence of modern western science. The method used is descriptive qualitative. Interpretive analysis is used to analyze data. The essence of interpretive analysis is located in the description of the concept of Islamization of Science. The method of interpretation is an analysis to achieve a correct understanding of the human expression being studied. The Islamization of knowledge is not only a discourse, but requires real implications to be useful for the wider community. The movement was carried out by sticking to the principles of monotheism so as not to deviate from religious teachings. Some developments have also taken place in Indonesia in response to the Islamization of science, including: the establishment of Islamic-based schools and the rise of cooperatives and Islamic banks.Keywords: Science, Islamization, and Modern Science.